Green Growth and Beyond: The Influence of Environmental Practices, Financial Management, Market Access, and Digital Integration on the Resilience and Sustainability Business Practices of MSMEs in Indonesia - Joeliaty, Joeliaty (IJBLE Scientific Publications Community Inc., 2024)
This study looks into how market accessibility, digital integration, financial management, and environmental practices affect the sustainability and resilience of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia. Data analysis is done using Structural Equation Modeling with Partial Least Squares (SEM-PLS) in a quantitative manner using a sample of 274 MSMEs. The diversity of the sample with respect to industry sectors, geographic regions, and company sizes is demonstrated by descriptive statistics. The structural model findings show positive and substantial correlations between the elements under investigation and company resilience and sustainability, while the measurement model analysis validates the validity and reliability of the constructs. The results are stable, as supported by bootstrapping analysis, and the model fit indices show good predictive relevance. The findings are interpreted in the discussion, which also provides policymakers and business practitioners with useful insights. The study adds to our theoretical understanding of MSME dynamics and offers guidance on how to develop resilient and sustainable business practices.